Adsorption of Azo Dye (AR 138) onto Acid Activated Bentonite Layered Cu and TiO2 Catalyst - Hashemian, Saeedeh (Asian Journal of Chemistry, 2011)
The acid activation bentonite supported TiO2 and Cu(II) ion as adsorbent-catalyst materials in aqueous solution was prepared. The decomposition of AR 138 dye in presence and in absence of H2O2 investigated. Adsorption of acid red 138 from aqueous solutions onto adsorbent under different condition was investigated. This powder adsorbent showed excellent adsorption towards AR 138 dye in acidic media (pH 2) and contact time 90 min. Strong preferential adsorption to A-Ben/TiO2 was observed. Comparatively, in the absence of H2O2, per cent of AR 138 dye removal was lower than in the presence of H2O2. The Langmuir and Freundlich adsorption models were applied to describe the equilibrium isotherms and isotherm constants were determined. The Freundlich model agrees well with experiment data.